MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA KERTAS LIPAT (ORIGAMI) PADA POKOK BAHASAN SEGITIGA SISWA KELAS IV SD SWASTA BHARLIND SCHOOL - Simamora, Lusiana; Simamora, Herna Jusnita (Jurnal Ilmiah Aquinas, 2022)
This type of research is classroom action research on the subject of triangles. The purpose of this research is to improve and/or improve learning practices in schools. The data collection tools used in this study were observation sheets and tests. Based on the results of the first cycle of learning, the results of the implementation of teacher activity learning are 60% with sufficient categories and the results of student observation sheets are 63.6 in the sufficient category, meaning that learning has not reached the criteria for good learning implementation. Student learning outcomes in the first cycle with an average of 69.2 with individual student learning completeness is 13 people, while the second learning outcomes with improvements in the implementation of learning on teacher activities obtained 79.7% with good category and the results of the implementation of learning on student activities obtained 80 with good category, individual learning completeness is 23 students, while classical completeness is with an average value of 80.6.